Diamond boy - Williams, Michael, 1962- (Little, Brown and Company, 2014)
"When Patson's family moves to [the] Marange region of Zimbabwe, he begins working in the mines, searching for blood diamonds, until government soldiers arrive and Patson is forced to journey to South Africa in search of his missing sister and a better life"--